Pengaruh Budaya Tri Hita Karana, Komitmen Organisasi, Dan Whistleblowing System Terhadap Pencegahan Fraud Pada LPD Se-Kecamatan Abang Karangasem - Ni Luh Ade Lisa Puja Gayatri; Sang Ayu Putu Arie Indraswarawati; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2022)
The purpose of this study is to find out the influence of tri hita karana culture, organizational commitment, and whistleblowing system to fraud prevention in LPD Se-Subdistrict Abang Karangasem. The number of populations in this study is all employees in LPD in Abang Subdistrict which amounts to 85 people from 20 LPDs, so all populations are used as research samples by sampling in this study is by saturated sample techniques or census. The data collection technique uses a questionnaire where the instrument will be tested first and then followed by a classic assumption test, then a double linear regression analysis, determination coefficient test, F test and T test. The results in this study are 1) Tri hita karana culture has a positive significant effect on lpd fraud prevention in Abang Subdistrict. 2) Organizational commitment has a positive significant effect on the prevention of LPD fraud in Abang District. 3) Whistleblowing system has a positive significant affects the prevention of LPD fraud in Abang District. The advice given to LPD in Abang Karangasem District is how to maintain behavior in accordance with applicable norms, improve good relations while working in the organization and increase the container for whistleblowers if they have the intention to make complaints related to fraud on LPD.